Idade penal: aspectos relevantes da punibilidade no ordenamento jurídico brasileiro - Moraes, Laura Rolim de (2008)
In Brazil, the matter relating to the legal age for the purposes of attributing liability to a minor who violates the law has been in focus for many years and has been the object of much controversy in the public eye, not to mention most jurists and legal experts who have strongly opposed the legal age reduction from eighteen (18) to sixteen (16) years, as intended by some government representatives who submitted more than twenty bills of amendments to the constitution motivated by a rising number of teenager criminality occurrences in the recent past, particularly in respect to some cases over which there has been quite a commotion in public opinion. Such a complex subject-matter requires a priority assignment by the governmental bodies and a most effective participation of society in seeking a satisfactory outcome. Although it represents a step ahead in the context of the issue, the special law which provides for the matter, namely the Estatuto da Criança e do Adolescente , has proved inefficient and unsatisfactory as regards teenagers, both in theory, comprehending certain faults which require review and correction, and in practice as well, due to not fulfillment of the purposes intended by it. Nevertheless, imputing liability at the age of sixteen would not relate to all crimes, but only to those considered more grievous and which presume a more impetuous behavior of the wrongdoer; such as, for example, the cases of homicide, rape, drug dealing, etc., which crimes are considered heinous [ hediondos ] by our currently applicable legislation. We tried to frame the most relevant aspects of a possible punitive action against minors who violate the laws, at all times bearing in mind to mention either side, as well as the aspects relating to an anti-crime oriented policy. In the present context, due to controversial opinions of well known jurists, insertion of the issue in the text of the constitution, which amendment involves controversy and delay, insufficient resources to implement a successful policy against crimes involving young people, the thesis of legal age reduction is very unlikely to succeed